European Union policy on pesticides: implications for agriculture in Ireland. Issue 11 (5th June 2014) - Jess, Stephen; Kildea, Steven; Moody, Aidan; Rennick, Gordon; Murchie, Archie K; Cooke, Louise R
Abstract European Community (EC) legislation has limited the availability of pesticide active substances used in effective plant protection products. The Pesticide Authorisation Directive 91/414/EEC introduced the principle of risk assessment for approval of pesticide active substances. This principle was modified by the introduction of Regulation (EC) 1107/2009, which applies hazard, the intrinsic toxicity of the active substance, rather than risk, the potential for hazard to occur, as the approval criterion. Potential impacts of EC pesticide legislation on agriculture in Ireland are summarised. While these will significantly impact on pesticide availability in the medium to long term, regulations associated with water quality (Water Framework Directive 2000/60/EC and Drinking Water Directive 1998/83/EC) have the potential to restrict pesticide use more immediately, as concerns regarding public health and economic costs associated with removing pesticides from water increase. This rationale will further reduce the availability of effective pesticide active substances, directly affecting crop protection and increasing pesticide resistance within pest and disease populations. In addition, water quality requirements may also impact on important active substances used in plant protection in Ireland. The future challenge for agriculture in Ireland is to sustain production and profitability using reduced pesticide inputs within a framework of integrated pest management. © 2014 Society of Chemical Industry